Venous thromboembolism in patients hospitalized for knee and hip joint replacement surgery. (25th November 2020) - Keller, K; Hobohm, L; Barco, S; Schmidtmann, I; Munzel, T; Engelhardt, M; Eckhard, L; Konstantinides, S; Drees, P
Abstract: Background: Venous thromboembolism (VTE) is a frequent acute cardiovascular disease, leading to significant morbidity and mortality worldwide. Major trauma, surgery, immobilisation and joint replacements are major provoking factors for VTE. In particular, patients undergoing knee and hip joint replacement surgery are at high risk of developing VTE perioperatively, even in the era of established pharmacological thromboprophylaxis. Without thromboprophylaxis, as many as 20–60% of patients may develop perioperative VTE. Purpose: As recent studies indicate an increasing number of total knee and hip replacement surgeries in European countries and the United States, aims of our study were to investigate a) total burden and temporal trends of VTE complications following knee (KJR) and hip joint replacement (HJR) in Germany 2005–2016 and to identify b) predictors of VTE during hospitalization. Methods: In an analysis of the nationwide German inpatient sample, we included all hospitalized patients with elective primary KJR and HJR in Germany between 2005 and 2016 (source: Research Data Center (RDC) of the Federal Statistical Office and the Statistical Offices of the federal states, DRG Statistics 2005–2016, own calculations). We analyzed temporal trends of surgical procedure, mortality, and VTE, and identified predictors of VTE. Results: A total of 1, 804, 496 hospitalized patients underwent KJR (65.1% women, 53.4% aged ≥70 years) and 1, 885, 839 received HJR (59.1% women, 51.4% ≥70 years). VTE was documented in 23, 297 (1.3% of total) KJR patients and in 11, 554 HJR patients (0.6%). The number of primary KJR (129, 832 in 2005 to 167, 881 in 2016 [β-(slope)-estimate 1978 per year; 95% CI 1951 to 2004, P<0.001]) and primary HJR (145, 223 in 2005 to 171, 421 in 2016 [β-estimate 1818 per year; 95% CI 1083 to 2553, P<0.001]) increased during this twelve-year period. In-hospital VTE decreased from 1.9% to 0.9% (β-estimate −0.77 [95% CI: −0.81 to −0.72], P<0.001) after KJR and from 0.9% to 0.5% (β-estimate −0.71 (95% CI: −0.77 to −0.65), P<0.001) after HJR. In parallel, in-hospital death rate dropped from 0.14% (184 deaths) to 0.09% (146 deaths) (β-estimate −0.44 [95% CI: −0.59 to −0.30], P<0.001) after KJR and from 0.33% to 0.29% (β-estimate −0.11 (95% CI: −0.20 to −0.02), P=0.018) after HJR. Infections during hospitalization were associated with a higher VTE risk. VTE events were associated with in-hospital death in KJR (OR 20.86 [95% CI: 18.78–23.15], P<0.001) and HJR (OR 15.19 [95% CI: 14.19–16.86], P<0.001) independently from age, sex and comorbidities. Conclusions: While total numbers of KJR and HJR interventions increased in Germany between 2005 and 2016, the rate of VTE decreased substantially. VTE complications were associated with 15-to 21-fold increase of in-hospital case-fatality rate. Perioperative infections increased the risk for VTE substantially. Funding Acknowledgement: Type of funding source: Public grant(s) – National budget only. Main funding source(s): This study was supported by the German Federal Ministry of Education and Research (BMBF 01EO1503), institutional grant for the Center for Thrombosis and Hemostasis. The authors are responsible for the contents of this publication.